Geomatic methods applied to the study of the front position changes of Johnsons and Hurd Glaciers, Livingston Island, Antarctica, between 1957 and 2013 - Rodríguez Cielos, Ricardo; Aguirre de Mata, Julián; Díez Galilea, Andrés; Álvarez Alonso, Marina A.; Rodríguez Cielos, Pedro; Navarro Valero, Francisco José (Earth System Science Data, 2016)
Various geomatic measurement techniques can be efficiently combined for surveying glacier fronts.Aerial photographs and satellite images can be used to determine the position of the glacier terminus. If theglacier front is easily accessible, the classic surveys using theodolite or total station, GNSS (Global NavigationSatellite System) techniques, laser-scanner or close-range photogrammetry are possible. When the accessibilityto the glacier front is difficult or impossible, close-range photogrammetry proves to be useful, inexpensive andfast. In this paper, a methodology combining photogrammetric methods and other techniques is applied to deter-mine the calving front position of Johnsons Glacier. Images taken in 2013 with an inexpensive nonmetric digitalcamera are georeferenced to a global coordinate system by measuring, using GNSS techniques, support points inaccessible areas close to the glacier front, from which control points in inaccessible points on the glacier surfacenear its calving front are determined with theodolite using the direct intersection method. The front positionchanges of Johnsons Glacier during the period 1957–2013, as well as those of the land-terminating fronts of Argentina, Las Palmas and Sally Rocks lobes of Hurd glacier, are determined from different geomatic techniquessuch as surface-based GNSS measurements, aerial photogrammetry and satellite optical imagery. This providesa set of frontal positions useful, e.g., for glacier dynamics modeling and mass balance studies.